Influence of citrus rootstocks on growth performance and leaf mineral nutrition of ‘Salustiana’ sweet orange [Citrus sinensis (L). obsek] - Khan , Muhammad Nawaz; Hayat, Faisal; Asim, Muhammad; Iqbal, Shahid; Ashraf, Tehseen; Asghar, Sumeera (Journal of Pure and Applied Agriculture, 2024)
Citrus fruits rank first among all fruit species and are widely grown across the globe in tropical and subtropical areas. The monopolized cultivation of ‘Kinnow’ mandarin in Punjab needs a substituted potential scion cultivar like ‘Salustiana’ for the diversification of the citrus industry of Pakistan. This current study was performed to examine the growth, vigour, photosynthesis, and nutrient utilization ability of ‘Salustiana’ orange (Citrus sinensis Osbeck L.) budded on one-year-old seedling of five rootstocks: ‘Carrizo citrange’ (Poncirus trifoliata (L) Raf × Citrus sinensis (L) Osbeck), ‘Troyer citrange’ (Poncirus trifoliata (L) Raf × Citrus sinensis (L) Osbeck), ‘Trifoliate orange’ (Poncirus trifoliata (L.), ‘Rangpur lime’ (Citrus limonia L. Osbeck) and ‘Rough